2017
DOI: 10.1177/2325967117708548
|View full text |Cite
|
Sign up to set email alerts
|

Early Graft Tunnel Healing After Anterior Cruciate Ligament Reconstruction With Intratunnel Injection of Bone Marrow Mesenchymal Stem Cells and Vascular Endothelial Growth Factor

Abstract: Background:Bone marrow mesenchymal stem cells (BM-MSCs) are multipotent adult stem cells and have become an important source of cells for engineering tissue repair and cell therapy. Vascular endothelial growth factor (VEGF) promotes angiogenesis and contributes fibrous integration between tendon and bone during the early postoperative stage. Both MSCs and VEGF can stimulate cell proliferation, differentiation, and matrix deposition by enhancing angiogenesis and osteogenesis of the graft in the tunnel.Hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…7 Therefore, GFs that enhance bone healing, such as bone morphogenetic proteins (BMPs), are becoming promising candidates to promote osteointegration of the graft, with special attention being given to the use of BMP-2. 6,9,16,26,28,30,32 However, the administration of soluble GFs is clinically challenging because of their low stability in the body and diffusion-related problems, which lead to the need for supraphysiological concentrations and systemic administration to achieve the desired result. 27 Additionally, Thomopoulos et al 34 showed that the addition of BMP-2 did not improve bone formation and mechanical properties when compared with a control in a canine flexor tendon.…”
mentioning
confidence: 99%
“…7 Therefore, GFs that enhance bone healing, such as bone morphogenetic proteins (BMPs), are becoming promising candidates to promote osteointegration of the graft, with special attention being given to the use of BMP-2. 6,9,16,26,28,30,32 However, the administration of soluble GFs is clinically challenging because of their low stability in the body and diffusion-related problems, which lead to the need for supraphysiological concentrations and systemic administration to achieve the desired result. 27 Additionally, Thomopoulos et al 34 showed that the addition of BMP-2 did not improve bone formation and mechanical properties when compared with a control in a canine flexor tendon.…”
mentioning
confidence: 99%
“…Besides, the fibrin glue applied in the graft-tunnel interface by Setiawati et al. [ 41 ] improved the graft press-fit to the walls of the femoral tunnel and reduced tunnel widening. Fibrin glue [ 42 ] was also useful to blend MSCs from bone to allograft to enhance the effect of MSCs and accelerated the osteointegration.…”
Section: Resultsmentioning
confidence: 99%
“…They proved that the combination of BMSCs and PRP synergistically stimulates tendon bone healing through stronger signals associated with angiogenesis, bone formation, and in situ tendon generation. Setiawati et al [ 64 ] then tested whether injecting BMSCs and vascular endothelial growth factor (VEGF) into the bone tunnel of rabbits after ACL reconstruction would improve the early healing process of a tendon graft. They found a higher mean collagen type III score, a higher value for the final tensile strength, as well as improved signal intensity for magnetic resonance imaging (MRI) in the group BMSCs + VEGF.…”
Section: Bmscsmentioning
confidence: 99%